Synthesis and Spectral Characterization of 4,7-Dichloro-6-nitroquinazoline - Thi Ngoc Nguyen; Thi Huong Tran; Nguyet Suong Huyen Dao; Van Giang Nguyen; Dinh Luyen Nguyen; Nguyen Trieu Trinh; Van Hai Nguyen (Molbank, 2020)
Afatinib is a 4-anilinoquinazoline tyrosine kinase inhibitor (TKI) in the form of a dimaleate salt which is indicated for the treatment of locally advanced or metastatic non-small cell lung cancer (NSCLC). The most scalable route for the synthesis of this drug was reported in two Boehringer Ingelheim patents, in which the title compound, 4,7-dichloro-6-nitroquinazoline (IV), is an important intermediate. Compound IV is also present in a number of synthetic pathways for various 4,7-disubstituted quinazoline derivatives displaying high therapeutic potential. However, no detailed characterization of this popular compound has been reported, possibly due to its high instability. In this paper, IV was prepared in an overall yield of 56.1% by a 3-step process (condensation, nitration, and chlorination) from 2-amino-4-chlorobenzoic acid (I). The target compound has been for the first time fully characterized by melting point, mass-spectrometry, FT-IR, 1H-NMR and 13C-NMR spectroscopies.